Improving knowledge dissemination and usage in new product development: the role of Product Data Management systems. (25th January 2011) - Codini, Anna
Although many Authors agree about the usefulness of Product Data Management (PDM) systems to stimulate knowledge dissemination, there are no many studies investigating if PDM systems really contribute to the usage of disseminated knowledge and about which are the challenges for implementing PDM systems. The aim of this paper is to clarify how PDM systems can improve the process of knowledge dissemination and usage and which PDM systems can do this. After the literature review, the paper reports a longitudinal case study of an Italian company aimed to analyse the changes occurred during the implementation of the PDM system over the time.